Raised by Wolves - Patterson, James, 1947-; Raymond, Emily, 1972- (New York : Little, Brown and Company, 2024)
"Two teens appear out of nowhere, ransacking a small-town grocery and attacking the police officers who come to investigate. Their clothes are torn and filthy, their hands and bare feet callused, they have fangs. They're sister and brother, alone against the world. Where did they come from? Raised by wolves, they say. Kai and Holo are taken in by the police chief and his wife, and begin adjusting to life in a small town, attending school and going on dates. But humans, they find, are the most vicious animals. And the mystery of their upbringing brings dark and powerful forces to Kokanee Creek, tearing the town apart and threatening the lives of everyone they love"--
Keywords: Siblings -- Fiction; Feral children -- Fiction; Wolves -- Fiction; Small cities -- Fiction; Thrillers (Fiction); Paranormal fiction